2008
DOI: 10.1002/jmri.21538
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of motion correction effect and image quality with the periodically rotated overlapping parallel lines with enhanced reconstruction (PROPELLER) (BLADE) and parallel imaging acquisition technique in the upper abdomen

Abstract: Purpose:To evaluate motion correction effect and image quality in the upper abdomen with the periodically rotated overlapping parallel lines with enhanced reconstruction (PROPELLER) (BLADE) and parallel imaging acquisition technique. Materials and Methods:A total of 50 consecutive patients underwent abdominal MR imaging. Fat-saturated T2-weighted turbo spin-echo sequences were obtained by respiratory triggering. The subjects were examined with three different conditions of echo train length (ETL), blade width,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 23 publications
1
50
0
3
Order By: Relevance
“…Recently, MRI techniques known as PRO-PELLER or BLADE have been introduced to address the motionartefact problem, which acquire k-space data using "blades" consisting of multiple parallel lines that are rotated in k-space in a radial-type scheme. [8][9][10][11] These techniques have demonstrated the substantial improvement in image quality for T 2 weighted 2D TSE acquisitions as well as diffusion-weighted imaging sequences. However, the significant overlap of the blades in k-space leads to inefficient k-space acquisition and, thus, to long acquisition times, which make it impractical to use these sequences for many clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MRI techniques known as PRO-PELLER or BLADE have been introduced to address the motionartefact problem, which acquire k-space data using "blades" consisting of multiple parallel lines that are rotated in k-space in a radial-type scheme. [8][9][10][11] These techniques have demonstrated the substantial improvement in image quality for T 2 weighted 2D TSE acquisitions as well as diffusion-weighted imaging sequences. However, the significant overlap of the blades in k-space leads to inefficient k-space acquisition and, thus, to long acquisition times, which make it impractical to use these sequences for many clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, PROPELLER or BLADE have been applied successfully in MR imaging of the brain to reduce motion artifacts in uncooperative or in pediatric patients [6][7][8][9] or to suppress flow artifacts 10,11 after application of contrast agent. Relevant benefits of PROPELLER or BLADE have also been reported in abdominal imaging, [12][13][14][15] but to our knowledge there are no data published on its application in spine imaging, except for a pilot study on 5 healthy volunteers. 16 Another important application of this technique is DWI, which is usually based on an echo-planar imaging sequence.…”
mentioning
confidence: 99%
“…BLADE has , c) shows that the node has an irregular border and that there is soft tissue infiltration of the muscle previously shown improvement in image quality by reducing patient motion artifacts [38] and pulsation artifacts related to vascular flow [39,40] and bowel peristalsis [41,42]. Although the study found that pulsation artifacts were reduced and upper thoracic structures were thereby better delineated, the TSE T1 technique showed better contrast between lymph nodes and fat.…”
Section: Rapid Mri Techniques For Detecting Nodal Diseasementioning
confidence: 85%